Toxoplasmic Infection-induced Injury in the Ileal Myenteric Plexus in Rats Depends on the Dose of Toxoplasma gondii Oocysts - Tironi, L. M. T.; Beraldi, E. J.; Borges, S. C.; Massocato, C. L.; Vieira, S. L. V.; Sant'ana, D. M. G.; Araújo, E. J. A.; Buttow, N. C. (Journal of Morphological Sciences, 2018)
Introduction The present study evaluated the effects of different inocula of Toxoplasma gondii oocysts on the ileal myenteric plexus in rats.Materials and Methods Male Wistar rats, 60 days old, were distributed into four groups: control group (CG; which received saline solution) and groups that were infected with 100 (TG100), 1000 (TG1000), and 5000 (TG5000) T. gondii oocysts. Thirty days after infection, the rats were sacrificed, and the ileum was collected to make whole-mount preparations that were subjected to immunofluorescence staining to observe the general neuronal population (HuC/D), nitrergic neurons (nNOS), and enteric glial cells (S100). Morphometric and quantitative analyses of myenteric neurons were performed.Results The infections with different T. gondii inocula did not cause neuronal or glial loss, but cause neuronal hypertrophy in general population and nitrergic subpopulation in infected groups. Conclusion: Changes in neuronal morphology were observed in the TG5000 group, including the presence of vacuoles, translocation of Hu protein to the nucleus, and dendritic distortions, suggesting functional alterations in these cells.
Keywords: dose; oocysts; toxoplasmosis; enteric nervous system; ileum